Health Literacy Levels and Predictors Among Lebanese Adults Visiting Outpatient Clinics in Beirut - Carmel H. Bouclaous; Samer Salem; Ahmad Ghanem; Namir Saade; Jad El Haddad; Melissa Bou Malham; Soad Al Osta; Karen Matar; Elma Nassar; Georges Yared; Majd Khiami; Mary Joe Eid (SLACK Incorporated, 2021)
Background: To date, there has been a dearth of research on health literacy in the Eastern Mediterranean Region and in particular Lebanon. Objectives: This cross-sectional study assessed the levels and correlates of health literacy in Lebanese adults. Methods: A total of 587 participants (54.5% women) were recruited from the outpatient clinics of five health facilities in Beirut. The questionnaire consisted of the Arabic version of the Functional Health literacy Scale, the Arabic short version of the European Health Literacy Survey, and questions on sociodemographic and health-related factors. Descriptive and inferential statistics were performed to assess the association of these factors with functional health literacy (FHL) and comprehensive health literacy (CHL) levels. Key Results: About 65.8% had inadequate or problematic FHL and 43.8% had inadequate or problematic CHL. Although FHL was negatively correlated with long-term illness, it was positively correlated with ability to pay and health status. CHL was positively correlated with education, income, ability to pay for treatment, health status, and FHL level, whereas it was negatively correlated with long-term illness. Binary logistic regression showed that low education, low socioeconomic status, and being a widow were predictive of inadequate FHL. Moreover, having inadequate FHL and low income increased the likelihood of having inadequate CHL. Conclusion: This study has identified those with risk factors for inadequate health literacy and unfavorable health outcomes. A national action plan can guide the promotion of health literacy and its embeddedness in society to instill competencies and the environment that would eliminate health inequities and sustain health in Lebanon. [HLRP: Health Literacy Research and Practice. 2021;5(4):e295-e309.] Plain Language Summary: This study examined health literacy levels and correlates in 587 Lebanese adults using two recognized screening tools. The first tool measured functional health literacy (FHL), which represents the ability of a person to acquire information on health through reading or writing. The second tool assessed comprehensive health literacy (CHL), which encompasses the ability of a person to use their social skills to acquire health information from different media and make appropriate health decisions based on this information. Close to two-thirds of the participants had inadequate or problematic FHL. More specifically, low education, low socioeconomic status, and widowhood were predictive of inadequate FHL. Nearly one-half of the participants had inadequate or problematic CHL with an increased likelihood of inadequate levels in people with low FHL and low income.